ISOLASI DAN KARAKTERISASI KHAMIR POTENSIAL PENGHASIL BIOETANOL DARI INDUSTRI ARAK DI KARANGASEM BALI - Simbolon, Nebay Cronika; Mahaputra Wijaya, I Made; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
This research aimed to isolate and identify potential yeast of bioethanol-producer from arak industri in Karangasem Bali. The isolated sample was taken from 3 different points from 2 villages in Karangasem Bali. Isolation was carried out using PYG media then purified to obtain pure isolates. The pure isolates were screened with several stages, namely a qualitative test of gas production, growth selection with the addition of antibiotics, and quantitative tests with an alcohol oxidation reaction. Determind by UV visible spectroscopy, 9 potential isolates was obtained to continue to the identification stage. At this stage fermentation was carried out in PYG media for 10 days using a starter from a potential isolate with a media glucose level of 20% of the media volume. Fementation results were then distilled. Of the obtained 9 potential isolates the best isolate. IS 258 isolates are determind the best isolates with 86.85 mL ethanol. The total ethanol produced by IS 258 is higher than with 60.73 mL alcohol control experiment (Alcotec). Isolate IS 258 was isolated from bayur skin samples taken from the sap fermentation process. IS 258 then identified macroscopically and microscopically. Based on the results of macroscopic and microscopic identification, IS 258 has many similarities with previous studies on yeast isolation, isolate IS 258 is presumably the yeast genus Saccharomyces sp. Further research is needed to optimize ethanol production of IS 258 and identify species from isolates IS 258. Keyword : bioethanol, Balinese wine, lau, yeast, isolation and identification of yeast, UV visible spectroscopy